The Contribution of Flexibility and Strength Training to the Results of Mawashi Geri's Kicks in Padangsidimpuan Male Athletes - Hendro Septiadi Sihombing; Albadi Sinulingga; Sabaruddin Yunis Bangun; Yan Indra Siregar (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
This study aims to determine the Contribution of Flekxibilty and Strenght Training to the Results of Mawashi Geri's Kick in Male Athletes of Dojo KOdim 0212 TS Padangsidimpuan City. The research method used is an experimental method. The population in this study amounted to 40 people. The sampling technique used is Purposive Sampling. The number of athlete samples used was 20 people. This study was carried out for 8 weeks with a frequency of exercise 5 times each week. From the calculation of data and hypotheses, namely the contribution of Flexibility and Strength training to the results of Mawashi Geri's Kick in male athletes of Dojo Kodim 0212 TS Kota Padangsidimpuan, shows that there is a significant contribution together between Flexibility and Strength training to the results of Mawashi Geri Kick in male athletes of Dojo Kodim 0212 TS Kota Padangsidimpuan. This illustrates that Flexibility and Strength training contributed to Mawashi Geri's kick results due to monitoring from the coach with the improvement in physical condition so that the calculation of data for the third hypothesis of the concurrent contribution of Flexibility and Strength training to Mawshi Geri's kick results was a significant contribution.